Développer chaque expression suivante :

A) (x+1) (x+2)
B). (x+2) (x+5)
C). (5+x) (x+1)
D). (x+2) (3+x)


Développer puis réduire chaque expression .

A) (x+1) (x-4)
B) (x+1) (x+2)
C) (x-1) (x-5 )
D(x-2 ) (3-x)

Développer une expression .

A) (x+5)²
B) (3-x)²
C) (2-a)²
D) (3y-4)²
e) (6-5x)²
F) (1-2a)²

1

Réponses

2014-09-24T20:00:49+02:00
Bonsoir



A = x² + 2x + x + 2

A = x² + 3x + 2


B). (x+2) (x+5)

B = x² + 5x + 2x + 10

B = x² + 7x + 10


C). (5+x) (x+1)

C = 5x + 5 + x² + x

C = x² + 6x + 5


D). (x+2) (3+x)

D = 3x + x² + 6 + 2x

D = x² + 5x + 6




 Développer puis réduire chaque expression .

A) (x+1) (x-4)

A = x² - 4x + x - 4

A = x² - 3x - 4

 
B) (x+1) (x+2)

B  = x² + 2x + x + 2

B = x² + 3x + 2


C) (x-1) (x-5 )

C = x² - 5x - x + 5

C = x² - 6x + 5
 D(x-2 ) (3-x)

Développer une expression .

A) (x+5)²

A = x² +10x + 25


B) (3-x)²

B = 9 - 6x + x²


C) (2-a)²

C = 4 - 4a + a²


D) (3y-4)²

D = 9y² - 24y + 16


e) (6-5x)²

E = 36 - 60x + 25x²


F) (1-2a)²

F = 1 - 4a + 4a²